Odd Graceful Labeling Of Tensor Product of Some Graphs (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
(G);E(G)) with p vertices and q edges, if there exists an injectionfunction : V (G) ! f0; 1; 2; ; 2q ô€€€ 1g with each edge uv assignedthe label jf(u)ô€€€f(v)j, the resulting edge labels are f1; 3; 5; ; 2qô€€€1g.The tensor product of two graphs, G and H, has a vertex setV (G) V (H) and an edge between (u; v) and (u0; v0), i both uu0 2 E(G) andvv0 2 E(H), here we denote tensor product by ^. In this paper, weprove Sn ^ Sm, Sn ^ Pm and Cn ^ Sm are odd graceful.